Burden of scrub typhus among patients with acute febrile illness attending tertiary care hospital in Chitwan, Nepal - Sangita Thapa; Pradip Hamal; Navin Kumar Chaudhary; Lokendra Bahadur Sapkota; Jaya Prasad Singh (BMJ Open)
Objectives Scrub typhus is an emerging neglected tropical disease, reported from many parts of Asia including Nepal. This study aims to determine the seroepidemiology of scrub typhus among febrile patients attending Chitwan Medical College Teaching Hospital (CMC-TH), Bharatpur, Nepal.Study design and setting This was a hospital laboratory-based prospective study conducted in CMC-TH (a 750-bed hospital) located in Bharatpur, Chitwan district of Nepal.Participants A total of 1797 patients visiting CMC-TH with acute febrile illness (temperature more than 38°C) were enrolled in this study.Methods A total of 1797 blood samples were collected from patients presenting with acute febrile illness. The samples were processed for detection of antibody for scrub typhus by ELISA for specific IgM antibody and Weil-Felix test.Results Out of 1797 serum sample of febrile patients, 524 (29.2%) were scrub typhus positive. Maximum seropositive cases were from Chitwan district, 271 (51.7%) with predominance among women, 314 (35.9%). Scrub typhus was common among age group 51–60 years (37.2%) and farmers, 182 (37.8%). Highest seropositivity was found in July, 60 (57.7%). Fever was common clinical symptom. Thrombocytopenia was seen in 386 (73.7%) and raised transaminase aspartate aminotransferase, 399 (76.1%) among seropositive cases. Weil-Felix test positive were 397 (22.1%) and IgM ELISA positive were 524 (29.2%). The correlation between IgM ELISA and Weil-Felix test showed statistically significant association (r=0.319, p<0.001).Conclusion High prevalence of scrub typhus implies that patients with acute febrile illness should be investigated for scrub typhus with high priority. There is utmost need of reliable diagnostic facilities at all levels of healthcare system in Nepal. Infection with scrub typhus was found high and this calls for an urgent need to introduce vaccine against scrub typhus. More sustain and vigorous awareness programmes need to be promoted for early diagnosis, treatment and control.